Epidemiological approach to identifying genetic predispositions for atypical hemolytic uremic syndrome - Sullivan, Maren; Erlic, Zoran; Hoffmann, Michael M.; Arbeiter, Klaus; Patzer, Ludwig; Budde, Klemens; Hoppe, Bernd; Zeier, Martin; Lhotta, Karl; Rybicki, Lisa A.; Bock, Andreas; Berisha, Gani; et al. (Annals of human genetics, 2010)
Atypical hemolytic uremic syndrome (aHUS) is caused by several susceptibility genes. A registry including analyses of susceptibility genes, familial occurrence and genotype-phenotype correlation should provide classification insights. Registry data of 187 unrelated index patients included age at onset, gender, family history, relapse of aHUS and potentially triggering conditions. Mutation analyses were performed in the genes CFH, CD46 and CFI and in the six potential susceptibility genes, FHR1 to FHR5 and C4BP. Germline mutations were identified in 17% of the index cases; 12% in CFH, 3% in CD46 and 2% in CFI. Twenty-nine patients had heterozygous mutations and one each had a homozygous and compound heterozygous mutation. Mutations were not found in the genes FHR1-5 and C4BP. In 40% of the patients with familial HUS a mutation was found. Penetrance by age 45 was 50% among carriers of any mutation including results of relatives of mutation-positive index cases. The only risk factor for a mutation was family history of HUS (p = 0.02). Penetrance of aHUS in carriers of mutations is not complete. Occurrence of homo- and heterozygous mutations in the same gene suggests that the number of necessary DNA variants remains unclear. Among clinical information only familial occurrence predicts a mutation.
Erstmals am 15 December 2009 online veröffentlicht
Gesehen am 06.09.2023